2020
DOI: 10.1002/app.49088
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of nanometer‐size grafted layer of quaternary ammonium polymer on poly(ether ether ketone) substrate

Abstract: Owing to its excellent physicochemical properties, poly(ether ether ketone) (PEEK) has been used clinically for medical implants. However, its surface properties should be improved to further enhance its compatibility with a living organism and infection resistance. Here, we examined the surface construction via a combined process, that is, the self‐initiated photoinduced graft polymerization of N,N‐dimethylaminoethyl methacrylate (DMA) on PEEK substrate followed by polymer quaternization using various bromoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…23 They were attributed to the phosphorus atom in the phosphate group and the nitrogen atom in the trimethylammonium group, respectively, in the phosphorylcholine group. 26,27 These results indicated that the MPC polymer layer was formed on the surface. 12,13 AFM is one of the most promising surface characterization tools that is capable of revealing the nanoscopic morphological features with high resolution.…”
Section: ■ Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…23 They were attributed to the phosphorus atom in the phosphate group and the nitrogen atom in the trimethylammonium group, respectively, in the phosphorylcholine group. 26,27 These results indicated that the MPC polymer layer was formed on the surface. 12,13 AFM is one of the most promising surface characterization tools that is capable of revealing the nanoscopic morphological features with high resolution.…”
Section: ■ Introductionmentioning
confidence: 79%
“…As previously reported, the hydrophilic nature and water-compatible characteristics of the MPC polymer coating contribute to the reduction of bacterial adhesion on the new lens surface. 15 , 25 , 61 …”
Section: Resultsmentioning
confidence: 99%
“…These macromolecules often mimic the physiochemical properties of AmPs leading to their antibacterial activity, while being more cost-effective and scalable . Some common examples include quaternary ammonium polymers, polymethacrylates, poly­[2-(dimethyl decyl ammonium)­ethyl methacrylate], poly-β-peptides, and polyimidazolium. , Guo et al investigated the relationship between polymer structure and antimicrobial properties of several antimicrobial compounds, finding a greater antibacterial efficacy in main-chain cationic polymers than side-chain cationic polymers. Overall, this study found that the side-chain/main-chain cationic polymers synthesized with small molecule cationic compounds, including imidazolium, quaternary ammonium, and 1,4-diazabicyclo[2.2.2]­octane-1,4-diium, had greater antibacterial efficacy than their corresponding small molecule cationic constituents.…”
Section: Recent Advances In Treatments For Bacterial Infectionsmentioning
confidence: 99%
“…Poly (ether ether) ketone (PEEK), which is a widely used material for bone implants, was photochemically modified by utilizing a "grafting to" approach by cationic, quaternary ammonium containing methacrylate polymer brushes, influencing cell-surface interaction [93]. The material had an anti-adhesive effect against E. coli, resulting in less than 1% of the bacteria adhering to the samples.…”
Section: Non-biodegradable Polymersmentioning
confidence: 99%
“…There are various polymers with good biocompatibility and biodegradable properties, which are preferred in the design of new materials [ 63 , 174 , 197 , 198 ]. Among the non-biodegradable polymers such as polyethylene (PE), polyethylene terephthalate (PET) or poly (ether ether) ketone (PEEK), there are some modified versions that may qualify as antimicrobial surfaces [ 60 , 92 , 93 ]. Most research studies, however, have focused on biodegradable polymers as these have the ability to be replaced by natural tissue [ 11 ].…”
Section: Conclusion and Perspectivementioning
confidence: 99%